STUDIES ON LYMPHOGRANULOMA VENEREUM : II. THE ASSOCIATION OF SPECIFIC TOXINS WITH AGENTS OF THE LYMPHOGRANULOMA-PSITTACOSIS GROUP - Rake, Geoffrey (The Rockefeller University Press, 1944)
Toxins, which resemble in most respects bacterial endotoxins, are associated with the agents of lymphogranuloma venereum, meningopneumonitis, and mouse pneumonitis as they grow in the yolk sac of the chick embryo. They are labile and are not readily separated from the bodies of the agent. They kill mice rapidly after intravenous, and in some cases after intraperitoneal, injection but the minimal lethal dose is relatively large and, in those freshly harvested yolk sacs which have been tested, has corresponded to about 36 million infective units. Characteristic lesions are produced in all mice except those which die very rapidly, and are found especially in the liver where necrosis of the midzone of the lobule occurs. Antitoxic sera which are effective against a few lethal doses of the toxin can be produced in rabbits or chickens by using either toxin or toxoid as antigen. Such sera behave in a manner analogous to antiendotoxins against bacterial endotoxins and they do not neutralize by the law of multiple proportions. Antitoxic sera can also be obtained from human beings convalescent from at least one of these diseases. The toxins and antitoxins appear to be highly specific and they may offer a useful tool in distinguishing between different members of this closely interrelated group.